Case Report: A case of lymph node metastatic cancer of unknown primary with elevated alpha-fetoprotein achieving long-term survival - Wang, Yan; Wang, Chao-Qun; Huang, Bi-Fei (Frontiers in Oncology, 2026)
IntroductionCarcinoma of unknown primary (CUP) is typically associated with a poor prognosis, with a median survival of less than one year. This article reports a rare case of an alpha-fetoprotein (AFP)-positive CUP patient who achieved a long-term survival of nearly five years, whose diagnostic and therapeutic course offers significant clinical insights.Case presentationA 67-year-old male patient presented with left neck lymphadenopathy. A comprehensive workup revealed no primary site, leading to a diagnosis of CUP. Although subsequent immunohistochemistry classified the case into the unfavorable prognostic subgroup, an individualized treatment strategy including three-drug combination chemotherapy based on the clinical suspicion of gastric cancer, targeted therapy with Apatinib, and localized radiotherapy, resulted in a remarkably long overall survival of 58 months. Serum AFP levels closely correlated with disease activity throughout the clinical course.ConclusionsThis case demonstrates that for CUP confined to lymph nodes, active and precisely reasoned individualized treatment can significantly improve prognosis, even in cases categorized as having an unfavorable prognosis. Furthermore, it underscores the necessity of immunohistochemistry for the accurate diagnosis of CUP and suggests that promoting precision medicine strategies may improve outcomes for these patients.